Evaluating the EVENODD Code: Principles, Applications, and Future Prospects in Data Storage Systems - Deng Jinxiang (ITM Web of Conferences)
In modern data storage and transmission, ensuring data integrity and reliability is critical due to potential losses or corruption caused by channel instability and system errors. Check codes have been developed to address these issues, allowing recovery of the original data even when errors occur. This paper provides a comprehensive analysis of the EVENODD code, a widely used parity code in error detection and correction applications. The fundamental principle of the EVENODD code relies on adding a binary check bit to ensure that the count of ones in the data string is either even or odd, depending on the desired configuration. Its implementation in Redundant Array of Independent Disks level 6 architecture highlights the code’s ability to improve data reliability by incorporating dual parity, enhancing fault tolerance in distributed systems. The advantages and limitations of EVENODD, such as its efficiency in single-bit error detection but inability to correct multi-bit errors, are examined. Additionally, comparisons are made with similar codes, including Longitudinal Redundancy Check and Cyclic Redundancy Check, to showcase their respective strengths and use cases. The paper discusses the EVENODD code’s industrial applications, particularly in satellite remote sensing and library databases, where data integrity is paramount. Future directions include optimizing the code's performance and cost-effectiveness for large- scale data storage and transmission environments, promoting secure and reliable information systems.